An Ecofriendly Alternative for the Removal of Cd (II) and Cu (II) from Aqueous Medium - Kour, Jagjit; Cagnin, M.; Homagai, P. L.; Pokhrel, M. R.; Ghimire, K. N.; Masi, A. (Journal of Nepal Chemical Society, 2013)
Different types of agricultural waste materials have been explored for their efficiency in removing heavy metal ions from aqueous solution. A biomass of Desmostachya bipinnata (DB) was investigated as the potential bio-adsorbent for the removal of Cd (II)) and Cu (II) from wastewater. The surface of DB was chemically grafted with ethylenediamine. It was characterized by elemental, FTIR and SEM analysis. The maximum adsorption capacity of MDB in the removal of Cd (II) and Cu (II) were 30.4mg/g and 41.6 mg/g at their optimum pH 6 and 5, respectively. The experimental data followed the Langmuir isotherm and pseudo-second order kinetic model The research results indicated that D. bipinnata can be an alternative, efficient and ecofriendly material for the removal of Cd (II) and Cu (II) from wastewater.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9333Journal of Nepal Chemical Society Vol. 30, 2012 Page:  37-44 Uploaded date: 12/16/2013